Biolegal Issues in the Establishment of An Historical Collection of Human Tissues: the case of the Project “Umbria Biobank” - Cippitani, Roberto; Colcelli, Valentina (Medicina Historica, 2021)
The project “Umbria Biobank” aims at setting up a biobank of human tissues for research purposes. The Umbria Biobank includes an historical archive established from the 1940s onwards by the former Institute of Pathological Anatomy of the University of Perugia and which collects at least 2.5 million tissue blocks and approximately 8 million cytological and histological slides, with accompanying documentation. This valuable collection, which has been maintained and improved over time, has remained largely unused due to several ethical issues and a lack of a specific regulation. In particular, as for other historical archives of diagnostic documentation, those materials and data have been collected at a time when there was not the awareness about the need of the authorisation of the patients, nor the idea that those materials and data would be useful for further research activities. The paper relates to the attempt of the biolegal team of the Project to avoid the destruction of important historical archives and to recover them for scientific research, in a legitimate way that respects fundamental rights. The solutions have to be elaborate within the context of the European Union, International and National legal sources.